Functional and morphological indicators of the sciatic nerve condition in rats in the long-term period after injury: A correlation analysis - Ziia K. Melikov; Oksana A. Rybachuk; Serhii I. Savosko; Volodymyr V. Likhodiievskyi; Yuriy G. Serozhkin; Alla I. Klimovskaya; Volodymyr V. Medvediev (Ukrainian Neurosurgical Journal)
Peripheral nerve injury (PNI) is a common pathology during wartime, significantly complicating the course and treatment of limb damage. Restorative treatment of PNI requires substantial improvement, which is impossible outside the methodology of experimental neurosurgery. The most frequently used PNI model involves transection of the rat sciatic nerve, followed by observation over 9–12 weeks and verification of results using functional-anatomical, electroneuromyographic, and morphometric methods. A key pathophysiological question—whether there is a correlation between the results of these three classes of research methods—remains a topic of ongoing debate. Objective: to determine the correlation between individual values of the sciatic functional index (SFI), the amplitude and latency of the M-response, as well as the density of nerve fibers in the injured sciatic nerve 12 weeks after its transection and neurorrhaphy. Materials and Methods. This study was conducted on adult male white outbred rats, selected from groups analyzed in a previous publication, which underwent electroneuromyographic and morphological examinations. In the sham-operated group (Sham; n=6), a surgical approach to the sciatic nerve was performed without nerve injury. In the Sect group (n=7), the sciatic nerve was transected in its middle third. In the Raph group (n=6), the stumps of the transected sciatic nerve were immediately sutured in an end-to-end way using several interrupted stitches. Twelve weeks post-surgery, SFI was calculated using the Bain–Mackinnon–Hunter formula. Additionally, the amplitude and latency of the M-response and specially calculated density of nerve fibers in three main sections of the sciatic nerve (proximal, central, and distal parts) were determined using longitudinal sections impregnated with silver nitrate (Sham — n=4, Sect — n=7, Raph — n=6). Quantitative data processing and statistical correlation analysis were performed using mathematical statistics tools. Results. Against the background of significant differences in the mean SFI values across all samples, a statistically significant difference was also found in the M-response amplitude for three pairs of sample comparisons, in the M-response latency (when comparing the values of the Sham and Sect groups, as well as the Sham and Raph groups), and in the density of nerve fibers (for the proximal part, central part or neuroma, and distal part of the nerve in three pairs of comparisons). Within each group, a statistically significant (strong negative) correlation was observed only between the M-response latency and the nerve fiber density in the distal section of the nerve in the Raph group. When combining the results from all groups into one cohort, significant correlations were found between individual values of the M-response amplitude and latency, SFI and M-response amplitude, SFI and M-response latency, SFI and nerve fiber density across all three nerve sections, M-response amplitude and nerve fiber density in all sections, and M-response latency and nerve fiber density in the central section of the nerve or neuroma. Conclusions. There is a correlation between the sciatic functional index, M-response amplitude and latency, and the density of sciatic nerve fibers. The statistical significance of these correlations becomes evident only with a sufficient number of observations and a broad range of individual values for the mentioned parameters.